Identifying community thresholds for lotic benthic diatoms in response to human disturbance - Tao Tang (Nature Portfolio, 2017)
Abstract Although human disturbance indirectly influences lotic assemblages through modifying physical and chemical conditions, identifying thresholds of human disturbance would provide direct evidence for preventing anthropogenic degradation of biological conditions. In the present study, we used data obtained from tributaries of the Three Gorges Reservoir in China to detect effects of human disturbance on streams and to identify disturbance thresholds for benthic diatoms. Diatom species composition was significantly affected by three in-stream stressors including TP, TN and pH. Diatoms were also influenced by watershed % farmland and natural environmental variables. Considering three in-stream stressors, TP was positively influenced by % farmland and % impervious surface area (ISA). In contrast, TN and pH were principally affected by natural environmental variables. Among measured natural environmental variables, average annual air temperature, average annual precipitation, and topsoil % CaCO3, % gravel, and total exchangeable bases had significant effects on study streams. When effects of natural variables were accounted for, substantial compositional changes in diatoms occurred when farmland or ISA land use exceeded 25% or 0.3%, respectively. Our study demonstrated the rationale for identifying thresholds of human disturbance for lotic assemblages and addressed the importance of accounting for effects of natural factors for accurate disturbance thresholds.